Entrepreneurship engineering: a structural perspective at manufacturing companies in Yazd City, Iran - Ziyae, Babak; Mohamed, Zainal Abidin (Faculty of Economics and Management, Universiti Putra Malaysia, 2009)
Corporate entrepreneurship (hereafter abbreviated as CE) plays a major role in promoting the performance of the small and medium sized enterprises (SMEs). To compete in the global market, it is imperative that company must know and understand the business environment (Zhang & Li, 2007). It is believed that companies that behave entrepreneurially and respond to the changing environment will perform better (Nybakk & Hansen, 2008). Entrepreneurship can also be conceptualized, however, as a process or activity within the organization, distinct from specific individuals. To encourage creativity, flexibility, and to support risk, it is a process of organizational renewal. This article hypothesized that more textile companies in Yazd city in Iran are encouraged to devote efforts towards identifying entrepreneurship engineering (here after acronym as EE), and determining which factors may affect the nature of this concept. The study employed the survey method using structured mail questionnaire. By quantitative methods, several textile companies in Yard city in Iran were examined in relation to EE. Data from twenty-five respondents in several carpet companies were analyzed. The findings show that EE as an important component can play vital role for improving organizational performance. Finally, the selected criteria have been assessed according to their relative importance by utilizing AHP approach and Expert Choice software program.